KAJIAN KUALITAS DAYA LISTRIK PLTS SISTEM OFF-GRID DI STT-PLN - Aas Wasri Hasanah; Tony Koerniawan; Yuliansyah Yuliansyah (Energi & Kelistrikan, 2018)
Inadequate power quality causes damage and may even cause damage to electrical equipment. Solar Power Plants Off-grid is a stand-alone power plant is not connected to the network. This system uses storage media such as batteries to maintain the availability of electricity at night or when the sun's intensity decreases. Solar power plant has a PV module that works based on the intensity of the captured sunlight and the inverter that can change the dc voltage into ac where as is known in the inverter there are non linear components which can result in poor quality of electrical power in this case the total harmonic distortion and voltage variations change. This may result in damage to electrical equipment. The electrical power quality of the STT-PLN off-grid PLTS will be analyzed and compared with the IEEE 519-1992 and SPLN 1: 1995 standards. Based on the results of the discussion that the THDi and THDv values ​​are still above the established standard limit of 5%.